Effects of Hydroxytyrosol in Endothelial Functioning: A Comprehensive Review - Ubashini Vijakumaran; Janushaa Shanmugam; Jun Wei Heng; Siti Sarah Azman; Muhammad Dain Yazid; Nur Atiqah Haizum Abdullah; Nadiah Sulaiman (Molecules, 2023)
Pharmacologists have been emphasizing and applying plant and herbal-based treatments in vascular diseases for decades now. Olives, for example, are a traditional symbol of the Mediterranean diet. Hydroxytyrosol is an olive-derived compound known for its antioxidant and cardioprotective effects. Acknowledging the merit of antioxidants in maintaining endothelial function warrants the application of hydroxytyrosol in endothelial dysfunction salvage and recovery. Endothelial dysfunction (ED) is an impairment of endothelial cells that adversely affects vascular homeostasis. Disturbance in endothelial functioning is a known precursor for atherosclerosis and, subsequently, coronary and peripheral artery disease. However, the effects of hydroxytyrosol on endothelial functioning were not extensively studied, limiting its value either as a nutraceutical supplement or in clinical trials. The action of hydroxytyrosol in endothelial functioning at a cellular and molecular level is gathered and summarized in this review. The favorable effects of hydroxytyrosol in the improvement of endothelial functioning from in vitro and in vivo studies were scrutinized. We conclude that hydroxytyrosol is capable to counteract oxidative stress, inflammation, vascular aging, and arterial stiffness; thus, it is beneficial to preserve endothelial function both in vitro and in vivo. Although not specifically for endothelial dysfunction, hydroxytyrosol safety and efficacy had been demonstrated via in vivo and clinical trials for cardiovascular-related studies.